2006
DOI: 10.4049/jimmunol.177.2.1017
|View full text |Cite
|
Sign up to set email alerts
|

High-Affinity Interactions between Peptides and Heat Shock Protein 70 Augment CD8+ T Lymphocyte Immune Responses

Abstract: Exogenously delivered antigenic peptides complexed to heat shock proteins (HSPs) are able to enter the endogenous Ag-processing pathway and prime CD8+ CTL. It was determined previously that a hybrid peptide containing a MHC class I-binding epitope and HSP70-binding sequence Javelin (J0) in complex with HSP70 could induce cytotoxic T cell responses in vivo that were more robust than those induced by the minimal epitope complexed with HSP70. The present study introduces a novel, higher-affinity HSP70-binding seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
44
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 63 publications
0
44
0
Order By: Relevance
“…The exact mechanism of the high immunostimulating activity of the fusion protein is not fully known, but it may be associated with previous reports indicating that HSPs play a varied role in enhancing the ability of APCs to stimulate T cells (6,10,44,45). In fact, the fusion protein induced the expression of higher levels of APC-associated molecules on DC than MMP did.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The exact mechanism of the high immunostimulating activity of the fusion protein is not fully known, but it may be associated with previous reports indicating that HSPs play a varied role in enhancing the ability of APCs to stimulate T cells (6,10,44,45). In fact, the fusion protein induced the expression of higher levels of APC-associated molecules on DC than MMP did.…”
Section: Discussionmentioning
confidence: 82%
“…Further, HSPs of both mammalian host cell and bacterial origins are reported to have chaperon activity (6,44) and can effectively prime a cytolytic response (10,45). In fact, we previously reported that HSP70 effectively induced the cross-priming of CD8 ϩ T cells through the cytosolic pathway when secreted from recombinant BCG in the phagosome of DC as part of a fusion protein (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, we used heat shock protein 70 (HSP70) (21)(22)(23)(24). The gene encoding HSP70 was directly connected with that of MMP-II and was extrachromosomally transformed into BCG (production of BCG-70M).…”
mentioning
confidence: 99%